Clean Coal Technologies in China: Current Status and Future Perspectives. (December 2016) - Chang, Shiyan; Zhuo, Jiankun; Meng, Shuo; Qin, Shiyue; Yao, Qiang
Abstract: Coal is the dominant primary energy source in China and the major source of greenhouse gases and air pollutants. To facilitate the use of coal in an environmentally satisfactory and economically viable way, clean coal technologies (CCTs) are necessary. This paper presents a review of recent research and development of four kinds of CCTs: coal power generation; coal conversion; pollution control; and carbon capture, utilization, and storage. It also outlines future perspectives on directions for technology research and development (R&D). This review shows that China has made remarkable progress in the R&D of CCTs, and that a number of CCTs have now entered into the commercialization stage.